The Effectiveness Of Online Learning In Mathematics Class 5 In Elementary School - Asri Pujilestari; Mustaji Mustaji; Suhari Suhari (Journal on Education, 2023)
This study aims to identify and describe planning, implementation, evaluation, inhibiting factors and inhibiting factors as well as efforts to resolve obstacles to online learning of class V mathematics at SDN Gugus 4, Bagor District, Nganjuk Regency. This research is a type of qualitative descriptive research using data collection techniques through questionnaires, observation sheets, interviews, and documentation. The research respondents were teachers, parents and students at SDN Gugus 4, Bagor District, Nganjuk Regency, with a total of 142 students, 6 teachers and 5 parents. The results of the study showed that (1) the teacher had carried out the planning of online learning for the fifth grade mathematics subject as outlined in the form of lesson plans, (2) the implementation of online learning for the fifth grade mathematics subject could be carried out properly where students stated that the teacher had managed online learning well, the responses and activities of students are happy, they can prepare themselves, they are actively involved, where the learning outcomes obtained are good, (3) The evaluation of online learning for the fifth grade mathematics subject has been carried out by the teacher who can explain that the learning carried out runs effectively with increase in learning outcomes of class V mathematics subject, (4) Supporting factors for online learning of class V mathematics subject, namely the existence of an internet network, the ability of human resources to carry out management related to online learning, (5) Factors inhibiting online learning of class V mathematics subject complained of by teachers, parents of students a and students are unstable networks, and (6) Efforts that can be made by the teacher are conducting learning using multimedia such as video, audio, CD-ROM based and collaborating with parents of students related to supervising students when conducting online learning at home.